Clinical observation of C3-type patellar fractures treated by operation methods with or without a turned-over patella. Issue 4 (April 2019) - Yin, Qu-dong; Wang, Jian-bing; Gu, San-jun; Wu, Yong-wei; Rui, Yong-jun
Highlights: Patella turned over method shortened the bedridden time but increased the range of motion (ROM) of knee joint. The Lysholm score was slightly elevated with patella turned over method. The patella turned over operation method is effective in treating C3-type patellar fractures. Abstract: Objective: To evaluate the clinical efficacy of operation methods with or without a turned-over patella for treatment of C3-type patellar fractures. Methods: A total of 68 patients with C3-type patellar fractures undergoing open reduction and internal fixation were retrospectively selected and treated with a turned-over patella surgery (turned-over patella group, n = 30) or conventional therapy without turning over the patella (conventional group, n = 38). The intraoperative and postoperative indicators of the two groups were assessed and comparatively analyzed. Results: The bedridden time was significantly shorter in the turned-over patella group than in the conventional group (P = 0.002), while the range of motion (ROM) of knee joint was significantly higher in the turned-over patella group (P = 0.044). The Lysholm score was slightly higher in the turned-over patella group than in the conventional group, but the difference was not statistically significant (P = 0.055). No significant difference was observed between the two groups in terms of the operation time (P = 0.096), intraoperative blood loss (P = 0.543), time of weight bearing (P = 0.312), fracture healing time (P = 0.272), or complications (P = 1). Conclusion: The turned-over patella operation method exhibited some superiority to conventional reduction-fixation approach for treatment of C3-type patellar fractures in terms of efficacy and safety by enlarging the ROM of the knee joint and promoting functional recovery.